Ajaran Gereja Katolik Tentang Hidup dan Kesehatan - Hadiwardaya, Aloysius Purwa (Jurnal Orientasi Baru, 2007)
Our life is a divine gift. It belongs to God, the Creator. We are not the masters. We are only ministers of our life. We are called to defend it and always take care of its integrity, as much as it is possible. Concretely speaking, we are expected to look after our own health as well as of that of others. From the perspective of Christian faith, we need to say that God, the Creator, does not expect something beyond our human capability. We are called only to do what we really can do.